2012
DOI: 10.1021/jp300932b
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Dissociation of CO2 to CO on Defective Surface of Cu(I)/TiO2–x Nanoparticles at Room Temperature

Abstract: The activation of CO2 on defective surface of Cu(I)/TiO2–x has been studied using in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS). It was demonstrated that CO2 – species, generated upon an electron attachment to CO2, are spontaneously dissociated into CO even in the dark on a partially oxygen depleted Cu(I)/TiO2–x surface prepared by thermal annealing in an inert environment. The formation of CO bound on Cu+ sites was identified in the DRIFT spectra, and isotopic carbon-labeling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
251
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 284 publications
(270 citation statements)
references
References 40 publications
15
251
1
3
Order By: Relevance
“…The surface oxygen vacancies play very important roles in governing the adsorption, activation and dissociation of CO 2 , which provide not only an electronic charge (Ti 3+ ) but also the sites for the adsorption of oxygen atoms from CO 2 [283]. It was even demonstrated that CO 2 − species, generated upon an electron attachment to CO 2 , are spontaneously dissociated into CO on defective Cu(I)/TiO 2−x at room temperature even in the dark [283].…”
Section: Important Factors Affecting Co 2 Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface oxygen vacancies play very important roles in governing the adsorption, activation and dissociation of CO 2 , which provide not only an electronic charge (Ti 3+ ) but also the sites for the adsorption of oxygen atoms from CO 2 [283]. It was even demonstrated that CO 2 − species, generated upon an electron attachment to CO 2 , are spontaneously dissociated into CO on defective Cu(I)/TiO 2−x at room temperature even in the dark [283].…”
Section: Important Factors Affecting Co 2 Activationmentioning
confidence: 99%
“…It was even demonstrated that CO 2 − species, generated upon an electron attachment to CO 2 , are spontaneously dissociated into CO on defective Cu(I)/TiO 2−x at room temperature even in the dark [283]. Indrakanti et al [249] performed the excited-state ab initio calculations of CO 2 adsorbed on clusters from the (010), (101), and (001) anatase surface planes.…”
Section: Important Factors Affecting Co 2 Activationmentioning
confidence: 99%
“…In addition to theoretical calculations (Markovits et al, 1996;Pan et al, 2009;He et al, 2010;Indrakanti et al, 2011;Pipornpong et al, 2011;Rodriguez et al, 2012), various microscopic (e.g., scanning tunneling microscopy (STM)) (Lee et al, 2011;Sutter et al, 2011) and spectroscopic (e.g., diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS), electron paramagnetic resonance (EPR)) (Schilke et al, 1999;Ulagappan and Frei, 2000;Wu and Huang, 2010;Dimitrijevic et al, 2011;Yang et al, 2011;Liu et al, 2012a;Shkrob et al, 2012) studies have been conducted to understand the steps associated with CO 2 adsorption, activation, and dissociation. These steps are found to be significantly affected by crystal phases (e.g., anatase, rutile), surface acidic-basic sites (e.g., hydroxyl group), defect disorders (e.g., oxygen vacancy (V O )), co-adsorbates (e.g., H 2 O), and electronic structure (e.g., charge transport) of TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Particularly in the case of gas/solid reactions, these deposited metals generate new catalytic sites. For example, isolated surface Cu + sites on TiO 2 promoted CO 2 photodissociation to CO [73], and surface Fe 3+ cations enhanced maleic acid photooxidation [74]. Metal cations like Cu, V, or Cr loaded onto TiO 2 during the sol-gel procedure raised NO photooxidation because it enhanced adsorption [75].…”
Section: Change Of Tio 2 Surface Speciationmentioning
confidence: 99%